KAB Newsletter Issue 02 (April-June 2022) - Sempungu, Joseph Godfrey; Nowamani, Collins (Kabale University, 2022)
IN THIS ISSUE; The KAB Chancellor presides over the 6th graduation The Vice Chancellor’s Tribute to Frank Kalimuzo KAB joins the Association of African Universities KAB hosts the Kiswahili international Conference - CHAKAMA Medical and Dental Practitioners Council Inspect KABSOM Patriotism Corps launched at KAB Kabale University Academic Staff Association (KABASA) elects new leaders Farmer Field schools changing the livelihoods of families in Kigezi Faculty of Social Sciences to launch Anti-Corruption Center Equal Opportunities Commission trains KAB Staff UNDP team visits Kabale University KAB hosts Italian Visitors